ANALYSIS OF POVERTY AS A MAIN PROBLEM OF THE INDONESIAN ECONOMY AND ITS OVERCOME - Qulsum, Umi; Anggraini, Jihan; Putri, Erisha (Academic Solution Publisher, 2024)
Poverty is a phenomenon that occurs in almost every developing country. Poverty stems from the inability of some people to organize their lives at a level that is considered humane. The problem of poverty is an unresolved problem in almost every country, including Indonesia. The research method used in this study was a literature study by examining various literature related to the topics discussed. The purpose of this research is to analyze poverty in Indonesia. The results of the analysis show that poverty in Indonesia can be caused by declining standards of global per capita income development, declining work ethic and people's productivity, low levels of education, and limited capital, these conditions reduce the quality of human resources, which leads to decreased productivity. and income. The reason is that the problem of poverty remains a major problem that needs attention and concrete action through the implementation of programs that are both recovery, empowering and facilitative. Therefore, the author wants to analyze poverty in Indonesia along with overcoming economic problems in Indonesia.